p47phox: A Central Regulator of NADPH Oxidase Function and a Promising Therapeutic Target in Redox-Related Diseases - Madison E. Gamble; Sruthi Sureshkumar; Maria Janina Carrera Espinoza; Natalie L. Hakim; Claudia M. Espitia; Fangchao Bi; Kevin R. Kelly; Wei Wang; Steffan T. Nawrocki; Jennifer S. Carew (Cells)
The NADPH oxidase 2 (NOX2) complex is a critical regulator of immune homeostasis. It is utilized by phagocytic leukocytes including neutrophils, monocytes, and macrophages to generate reactive oxygen species (ROS) that drive microbe clearance and modulate inflammatory responses. Within NOX2, the essential scaffold protein p47phox plays a pivotal role in orchestrating enzyme activation and facilitating the assembly and membrane translocation of cytosolic components of the complex. Tight regulation of p47phox activity is crucial, and its disruption is linked to a number of pathological conditions. Conversely, its hyperactivity contributes to oxidative stress, tissue damage, the progression of cardiovascular diseases, neurodegenerative disorders, inflammatory conditions, metabolic syndromes, and cancer. In this review, we detail the structural and functional roles of p47phox, mechanisms of its regulation, and its multifaceted contributions to disease pathogenesis. We explore the latest advances in p47phox-targeted therapeutic strategies, discuss current challenges in the field, highlight p47phox’s potential as a transformative target in redox biology and propose future directions to unlock its clinical utility.